Misoprostol for Termination of Second Trimester Pregnancy (Journal of Patan Academy of Health Sciences, 2015)
Introductions: The termination of second trimester pregnancy is challenging due unfavorable cervix. This study evaluate the efficacy and maternal side effects of intravaginal misoprostol for termination of second trimester pregnancy. Methods: During one year period from 15th June 2011 to 14th June 2012, Department of Obstetrics and Gynaecology of Patan Hospital, women admitted for second trimester termination of pregnancy for fetal congenital anomalies and intrauterine fetal demise were studied using the International Federation of Gynaecology and Obstetrics recommended doses of vaginal misoprostol. For congenital anomalies, 400 mcg 3 hourly to a maximum of 5 doses were used. For fetal demise, gestational age of 13-17 weeks received 200 mcg every 6 hourly to a maximum of 4 doses, and 18-26 weeks dose was adjusted to 100 mcg. Main outcome measures included success rate of abortion within 48 hours, induction to delivery interval and maternal side effects. Results: There were 40 patients during study period. Success rate for termination of 2nd trimester pregnancy within 48 hours was 88.8% for congenital anomalies. For fetal demise, success of termination was 90.9% at 13-17 weeks and 100% at 18-26 weeks. Median time from induction to delivery was 26.8 hours for congenital anomalies. For fetal demise, it was 18 hours for 13-17 weeks was and 24 hours at 18 to 26 weeks respectively. Abdominal pain was seen in all doses of misoprostol. Conclusions: Vaginal misoprostol is an effective method for termination of second trimester pregnancy. Plain Language Summary: The study was conducted to see the effectiveness of vaginal misoprostol for termination of second trimester pregnancy. The success rate of termination for congenital abnormality and fetal demise was high. Vaginal misoprostol was an effective method for termination of second trimester pregnancy. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13010 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):16-19